(5/ x-1)+(1/y-2)=2,(6/x-1)-(3/y-2) then the value of x
Answers
Answered by
1
Answer:
First equation:
x−1
5
+
y−2
1
=2
or,
(x−1)(y−2)
5(y−2)+x−1
=2
xy−2x−y+2
5y−10+x−1
=2
= x+5y−11=2xy−4x−2y+4
or ,x+5y−11+4x+2y−4=2xy
or, 5x+7y−15=2xy
second equation:
x−1
6
−
y−2
3
=1
xy−2x−y+2
6y−12−3x+3
=1
= 6y−3x−9=xy−2x−y+2
6y−3x−9+2x+y−2=xy
or, 7y−x−11=xy
Multiply the second equation by 2 and subtract first equation from resultant
14y−2x−22=2xy
7y+5x−15=2xy
------------------------------
7y−7x−7=0
y−x−1=0
y=x+1
Substituting the value of x in first equation, we get;
5x+7y−15=2xy
Or, 5x+7x+7−15−2x(x+1) Or, 12x−8=2x
2
+2x Or, 10x−8=2x
2
Or, x
2
=5x−4
Similarly, substituting the value of y in second equation, we get;
7y−x−11=xy
Or, 7x+7−x−11=x
2
+1 Or, 6x−5=x
2
From above two equations, it is clear
5x−4=6x−5
Or, 5x+1=6x
Or, x=1
Hence, y=x+1=2
Hence, x=1 and y=2
Similar questions